The relationship between functional independence and life satisfaction among Iranian community-dwelling older adults during the COVID-19 pandemic: A cross-sectional study - Mohammad Hossein Saghaei; Mohammad Saleh Poor Emran; Nima Sarouei; Morteza Zarekar; Shima Haghani; Shahzad Pashaeipour (Kashan University of Medical Sciences, 2023)
Background: The COVID-19 pandemic has fundamentally changed the lives of older adults. However, the functional independence (FI) and the life satisfaction (LS) of older adults have received less attention.Objectives: This study aimed to evaluate the relationship between FI and LS in community-dwelling older adults during the COVID-19 pandemic.Methods: This cross-sectional study was conducted in 2021. Participants were 479 community-dwelling older adults randomly selected from public healthcare centers in southern Tehran, Iran. Data collection instruments were a demographic questionnaire, the activities of daily living (ADL) scale, the Instrumental ADL (IADL) scale, and the Life Satisfaction Index-Z. The Pearson correlation coefficient, independent samples t-test, analysis of variance, and regression analysis were used to analyze the data.Results: The mean scores of participants' LS, FI in ADL, and FI in IADL were 11.94±5.11 (in the possible range of 0-26), 15±2.32 (in the possible range of 0-16), and 11.28±3.72 (in the possible range of 0-14), respectively. Around 55% of participants had low LS and only 2.5% of them had high LS. LS had a significant correlation with independence in ADL (r=0.133; P=0.004) and IADL (r=0.213; P<0.001). Independence in IADL and income significantly predicted 30% of the variance of LS (P<0.05).Conclusion: Older adults had optimal levels of FI in ADL and IADL and a low level of LS. Healthcare authorities can improve older adults' LS through strategies to promote their FI; such as formulating health policies, amending health system laws, and establishing insurance coverage to reduce costs.